2008
DOI: 10.1021/bi801283d
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation of an N-(Deoxyguanosin-8-yl)-2-acetylaminofluorene Adduct in the Active Site of Human DNA Polymerase ι: Hoogsteen or Watson−Crick Base Pairing?

Abstract: Bypass across DNA lesions by specialized polymerases is essential for maintenance of genomic stability. Human DNA polymerase ι (polι) is a bypass polymerase of the Y family. Crystal structures of polι suggest that Hoogsteen base pairing is employed to bypass minor groove DNA lesions, placing them on the spacious major groove side of the enzyme. Primer extension studies have shown that polι is also capable of error-free nucleotide incorporation opposite the bulky major groove adduct N-(deoxyguanosin-8-yl)-2-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 96 publications
2
20
0
Order By: Relevance
“…The APG base and DNA backbone are shifted out toward the major groove to achieve a standard C1′–C1′ distance for anti -guanine:dCTP Watson–Crick base pairing (Figure 2C and 3A). This observation is consistent with the prediction that Watson–Crick base pairing could occur in the polι active site for a major groove adduct by a previous modeling study (37). Thus, our APG-dCTP structure illustrates how polι can accommodate the APG lesion in Watson–Crick base pairing, a mechanism different from Hoogsteen base pairing observed in all the previous purine template structures of polι (33).…”
Section: Resultssupporting
confidence: 93%
“…The APG base and DNA backbone are shifted out toward the major groove to achieve a standard C1′–C1′ distance for anti -guanine:dCTP Watson–Crick base pairing (Figure 2C and 3A). This observation is consistent with the prediction that Watson–Crick base pairing could occur in the polι active site for a major groove adduct by a previous modeling study (37). Thus, our APG-dCTP structure illustrates how polι can accommodate the APG lesion in Watson–Crick base pairing, a mechanism different from Hoogsteen base pairing observed in all the previous purine template structures of polι (33).…”
Section: Resultssupporting
confidence: 93%
“…18,38,39 The resulting SMI is stabilized by various chemical interactions within the binding pocket and will hinder translocation during TLS. 18,36,56 For example, Schorr and Carell 41 showed that frameshift formation is triggered by the unstable base pairing of the AAF lesion with the correct incoming dC. Such configurations have been observed in replicative and bypass polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…Such configurations have been observed in replicative and bypass polymerases. 18,38,39,56 To this end, we reported the structures of the FAAF-modified Nar I-sequence corresponding to −1, −2, and −3 deletion duplexes. 33 These SMIs exist in a mixture of B- and S-SMI conformers, with the population of the S conformer and the thermodynamic stability being in the order of −1 > −2 > −3.…”
Section: Discussionmentioning
confidence: 99%
“…1c). Although this “wedge” W-conformer led to severe distortion of the DNA binding area in the active site of Pol iota (12), it is a distinct possibility in polymerase-free duplex DNA (13). …”
mentioning
confidence: 99%